Queer Sewing as a Way of Life:: resistances to neoconservatisms of race and gender - de Miranda, Shirley Aparecida; Peixoto da Silva, Jaime (Revista Brasileira de Estudos da Presença, 2024)
This article brings out strategies for confronting neoconservatisms of gender and race through what is here called queer sewing. Based on the narrative patches produced in doctoral research, the relationship between clothes and the norm is discussed. The concepts of ancestry and intersectionality are mobilized to problematize the remodeling of the self in the confrontation with cisheteronorm and normative whiteness. It was noticed that queer sewing can be seen as a strategic way of life, as it highlights a certain work on oneself on the part of the subject that speaks of an ethical way of existing in the world, a process in which not only clothes were pro-duced, but, mainly, a form of existence.